2014
DOI: 10.1093/cid/ciu019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of HIV-1 Drug Resistance Testing at Low-Level Viremia and Its Ability to Predict Future Virologic Outcomes and Viral Evolution in Treatment-Naive Individuals

Abstract: Routine HIV-1 genotyping of LLV samples can be performed with a reasonably high success rate, and the results appear predictive of future virologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 31 publications
5
66
2
Order By: Relevance
“…For example, the Sanger assay was able to amplify and to sequence successfully only ϳ40% of samples with pVLs of Ͻ1,000 copies/ml in this experiment. In contrast, our laboratory typically achieves a Ͼ85% success rate for samples with low pVLs if samples that initially fail to produce a PCR product are retested with a backup protocol (34). Furthermore, the sequencing success rates for the internal controls (pNL4-3 and POS08) were comparable to those of the clinical samples for both the Sanger (86%) and MiSeq (93%) assays.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the Sanger assay was able to amplify and to sequence successfully only ϳ40% of samples with pVLs of Ͻ1,000 copies/ml in this experiment. In contrast, our laboratory typically achieves a Ͼ85% success rate for samples with low pVLs if samples that initially fail to produce a PCR product are retested with a backup protocol (34). Furthermore, the sequencing success rates for the internal controls (pNL4-3 and POS08) were comparable to those of the clinical samples for both the Sanger (86%) and MiSeq (93%) assays.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the sample source, one of three PCR products was produced by nested PCR. Briefly, an amplicon spanning complete protease and RT codons 1 to 400 was produced for Canadian samples (34). In cases in which amplification of Canadian samples failed, backup amplification of a product covering protease and RT codons 1 to 240 was attempted (34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporting based on a more sensitive assay can potentially have significant repercussions on pharmacy costs and clinical outcomes. The clinical relevance of detecting these variants in HBV is still unclear (20)(21)(22), but experience in resistance testing for HIV patients with low viral loads (and rare mutations) has suggested that they may have long-term clinical impacts (23). With increased adoption of NGS for clinical applications, further study is required to understand the potential clinical impact of the additional information identified by NGS, such as low-level mutant subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…When economically feasible, resistance markers can be used to identify resistance before treatment and drugs chosen accordingly (personalized medicine). This is already the standard practice in the treatment of various bacterial 35,36 and HIV infections 37,38 in many countries, and could conceivably become so in malaria, at least in rich country or military settings. We contend that a fundamental challenge for this sort of personalized medicine will ultimately prove to be the amount of pathogen biomass that can be sampled and the ability of the molecular assay to detect very rare genotypes in that sample.…”
Section: Discussionmentioning
confidence: 99%